The Capulana study: a prospective evaluation of cervical cancer screening using human papillomavirus testing in Mozambique. Issue 9 (September 2020) - Salcedo, Mila P; Oliveira, Cristina; Andrade, Viviane; Mariano, Arlete A N; Changule, Dércia; Rangeiro, Ricardina; Monteiro, Eliane C S; Baker, Ellen; Phoolcharoen, Natacha; Varon, Melissa L; Thomas, Joseph P; Castle, Philip E; et al.
ABSTRACT : Background : Cervical cancer is the leading cause of cancer and related deaths among women in Mozambique. There is limited access to screening and few trained personnel to manage women with abnormal results. Our objective was to implement cervical cancer screening with human papillomavirus (HPV) testing, with navigation of women with abnormal results to appropriate diagnostic and treatment services. Methods : We prospectively enrolled women aged 30‐49 years living in Maputo, Mozambique, from April 2018 to September 2019. All participants underwent a pelvic examination by a nurse, and a cervical sample was collected and tested for HPV using the careHPV test (Qiagen, Gaithersburg, Maryland, USA). HPV positive women were referred for cryotherapy or, if ineligible for cryotherapy, a loop electrosurgical excision procedure. Women with findings concerning for cancer were referred to the gynecologic oncology service. Results : Participants (n=898) had a median age of 38 years and 20.3% were women living with the human immunodeficiency virus. HPV positivity was 23.7% (95% confidence interval 21.0% to 26.6%); women living with human immunodeficiency virus were twice as likely to test positive for HPV as human immunodeficiency virus negative women (39.2% vs 19.9%, p<0.001). Most HPV positive women (194 of 213, 91.1%) completed all steps of their diagnostic work‐up and treatment. Treatment included cryotherapy (n=158, 77.5%), loop electrosurgical excision procedure (n=30, 14.7%), or referral to a gynecologist or gynecologic oncologist (n=5, 2.5%). Of eight invasive cervical cancers, 5 (2.8%) were diagnosed in women living with human immunodeficiency virus and 3 (0.4%) in human immunodeficiency virus negative women (p=0.01). Conclusion : Cervical cancer screening with HPV testing, including appropriate follow‐up and treatment, was feasible in our study cohort in Mozambique. Women living with human immunodeficiency virus appear to be at a significantly higher risk for HPV infection and the development of invasive cervical cancer than human immunodeficiency virus negative women.